"TRANSPARENCY AND LIGHT, STRUCTURE AND SUBSTANCE": ENAMEL PAINTS IN LáSZLó MOHOLY-NAGY'S Z VII (1926). Issue 4 (November 2013) - Tsai, Joyce; Krueger, Jay; Maines, Christopher
Abstract : Z VII (1926), a painting by Hungarian-born artist László Moholy-Nagy in the collection of the National Gallery of Art, Washington, D.C., is striking for its richly varied surface, a quality unusual for his paintings from the period. Recent conservation treatment exposed a range of carefully calibrated and deliberate juxtapositions of smooth glossy and subtly textured matte paints on its surface. Subsequent scientific analysis conducted at the Gallery indicates that enamel paints were used discretely in several areas of the painting. This study addresses the use of these new materials in the artist's repainting of Z VII .